2010
DOI: 10.1002/jemt.20836
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature glycol methacrylate resin embedding method: A protocol suitable for bone marrow immunohistochemistry, PCR, and fish analysis

Abstract: In this article, an in situ observation method, combining laser scanning confocal microscopy and electron backscattering diffraction, was used to investigate the morphological and crystallographic evolution of bainite transformation in a Fe-0.15C binary alloy. The nucleation at a grain boundary and inclusions, sympathetic nucleation, and impingement event of bainitic ferrite were directly shown in real time. The variant evolution during bainite transformation and misorientation between bainitic ferrites were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…In previous resin embedding methods, benzoyl peroxide (BPO) and N, N-Dimethylaniline (DMA) were used as initiator and accelerator (called redox system) and polymerization temperatures at −20°C–4°C. 20 , 21 , 22 Considering the volume of the whole brain, the chemical polymerization method was unsuitable for embedding the whole brain or larger tissues during two days. Here, we tried to replace DMA with N, N-Dimethyl- p -toluidine (DMT), which has lower activation energy, higher the reaction rate, and shorter induction period ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous resin embedding methods, benzoyl peroxide (BPO) and N, N-Dimethylaniline (DMA) were used as initiator and accelerator (called redox system) and polymerization temperatures at −20°C–4°C. 20 , 21 , 22 Considering the volume of the whole brain, the chemical polymerization method was unsuitable for embedding the whole brain or larger tissues during two days. Here, we tried to replace DMA with N, N-Dimethyl- p -toluidine (DMT), which has lower activation energy, higher the reaction rate, and shorter induction period ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, this method had not yet been performed on large-volume tissue, not even on the whole mouse brain because it was difficult to maintain the integrity of large tissue samples. 19 , 20 In this study, we screened a variety of methods for the most suitable temperature for polymerization and chose the chemical polymerization method for its low polymerization temperature. We used a polymerization accelerator and screened for the optimal concentration, which could embed the whole brain stably in two days, improving the signal-to-background ratio.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Similar findings were obtained by Zhang et al (2010) on bone marrow specimens that were preserved in temperature of 24°C for 2 months. 25 The technique of DNA profiling is expensive and, moreover, it is a time consuming procedure. The data obtained in this study have indicated that DNA survival could be found in both saliva and blood samples until day 13 and 17 respectively, when the temperature reached 55°C.…”
Section: Fig 12: Bar Charts Shows Time-course Average Of Dna Recovermentioning
confidence: 99%
“…Second, the results have also indicated that DNA can be obtained from semen evidence even during the hot season because it can resist elevated temperature, probably because of the structure of the sperm head. 25 The success of forensic scientist in investigating a crime scene for evidence is the ability to profile samples for DNA survival successfully. 26 When a DNA sample has been degraded by any means, the average size of a DNA fragment might be reduced to less than 300 bp leading to insufficient DNA template, resulting in an inability to identify the individual.…”
Section: Fig 12: Bar Charts Shows Time-course Average Of Dna Recovermentioning
confidence: 99%
“…. With proper optimization, most special in situ and molecular studies are at least equally amenable to both embedding media as shown in many studies . Plastic embedding techniques may obviate the need for the decalcification step and thus eliminate one of the major variables impacting pre‐analytical bone marrow IHC quality.…”
Section: Special Considerations For Pre‐analytical Phasementioning
confidence: 99%